Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Câu 1:
a: \(\left(a+b\right)^3-3ab\left(a+b\right)\)
\(=a^3+3a^2b+3ab^2+b^3-3a^2b-3ab^2\)
\(=a^3+b^3\)
b: \(a^3+b^3+c^3-3abc\)
\(=\left(a+b\right)^3+c^3-3ab\left(a+b\right)-3abc\)
\(=\left(a+b+c\right)\left(a^2+2ab+b^2-ac-bc+c^2\right)-3ab\left(a+b+c\right)\)
\(=\left(a+b+c\right)\left(a^2+b^2+c^2-ab-ac-bc\right)\)
Sửa đề \(M=\left(1+\frac{a}{b}\right)\left(1+\frac{b}{c}\right)\left(1+\frac{c}{a}\right)\)
Ta có: \(a^3+b^3+c^3=3ab\)
\(\Leftrightarrow\left(a+b+c\right)\left(a^2+b^2+c^2-ab-bc-ca\right)=0\)
\(\Rightarrow\orbr{\begin{cases}a+b+c=0\\a^2+b^2+c^2-ab-bc-ca=0\end{cases}}\)
TH1: a+b+c=0
=> \(\hept{\begin{cases}a=-\left(b+c\right)\\b=-\left(a+c\right)\\c=-\left(a+b\right)\end{cases}}\)
Thay vào M ta được M=\(\left(1-\frac{b+c}{b}\right)\left(1-\frac{a+c}{c}\right)\left(1-\frac{a+b}{a}\right)\)
\(\Rightarrow M=\frac{-c}{b}\cdot\frac{-a}{c}\cdot\frac{-b}{a}=-1\)
TH2: \(a^2+b^2+c^2-ab-bc-ca=0\)
\(\Leftrightarrow\left(a-b\right)^2+\left(b-c\right)^2+\left(c-a\right)^2=0\)
\(\Rightarrow M=\left(1+1\right)\left(1+1\right)\left(1+1\right)=8\)
Ta có:
** \(a^3+b^3 +c^3 -3abc \)
\(=(a+b)^3+c^3 - 3ab(a+b) - 3abc \)
\(=(a+b+c)[(a+b)^2 - c(a+b)+ c^2] - 3ab(a+b+c) \)
\(=(a+b+c)(a^2 + 2ab+b^2-ca-bc+c^2) - 3ab(a+b+c) \)
\(=(a+b+c)(a^2+b^2+c^2-ab-bc-ca) \)
\(=a^2+b^2+c^2-ab-bc-ca\)
** \((a-b)^2 + (b-c)^2+(c- a)^2\)
\(=a^2+b^2+b^2+c^2+c^2+a^2 - 2(ab+bc+ca)\)
\(=2(a^2+b^2+c^2-ab-bc-ca)\)
\(\Rightarrow A=\dfrac{a^2+b^2+c^2-ab-bc-ca}{2\left(a^2+b^2+c^2-ab-bc-ca\right)}=\dfrac{1}{2}\)